2021
DOI: 10.1016/j.bbih.2021.100370
|View full text |Cite
|
Sign up to set email alerts
|

CCL4 induces inflammatory signalling and barrier disruption in the neurovascular endothelium

Abstract: Background During neuroinflammation many chemokines alter the function of the blood-brain barrier (BBB) that regulates the entry of macromolecules and immune cells into the brain. As the milieu of the brain is altered, biochemical and structural changes contribute to the pathogenesis of neuroinflammation and may impact on neurogenesis. The chemokine CCL4, previously known as MIP-1β, is upregulated in a wide variety of central nervous system disorders, including multiple sclerosis, where it is thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Ccl4 signaling sent from microglia 16 is enriched in PMX205 treated mice. Ccl4 stimulation has led to brain barrier disruption in vivo and in vitro [ 53 ], which can lead to increased PVM macrophage infiltration. Interestingly, in the PMX205 treated mice, both microglia 13 and 16 are sources of App signaling, which ligates to Cd74 receptors in PVM macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ccl4 signaling sent from microglia 16 is enriched in PMX205 treated mice. Ccl4 stimulation has led to brain barrier disruption in vivo and in vitro [ 53 ], which can lead to increased PVM macrophage infiltration. Interestingly, in the PMX205 treated mice, both microglia 13 and 16 are sources of App signaling, which ligates to Cd74 receptors in PVM macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This step of the study is shown schematically as a part of the general flowchart in Figure 3(b). The following biomarkers from the Top-10 IL6 97,98 , CSF1 99 , CXCL10 100 , PDGFA 101 , CCL2 102 are associated with aging, while the rest CXCL9 31 , CCL22 103 , PDGFB 104 , CCL4 105 , IL1RA 106 are associated with different age-related and inflammatory pathological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This step of the study is shown schematically as part of the general flowchart in Figure 3(b). Such Top-10 biomarkers as IL6 96,97 , CSF1 98 , CXCL10 99 , PDGFA 100 , CCL2 101 are associated with aging, and the other CXCL9 31 , CCL22 102 , PDGFB 103 , CCL4 104 , IL1RA 105 are associated with different age-associated and inflammatory pathological conditions. Figure 4(b) shows the relative distribution of the 10 selected immunological biomarker values and chronological age.…”
Section: Feature Selection and Dimensionality Reductionmentioning
confidence: 99%
“…Ccl4 signaling sent from microglia 16 is enriched in PMX205 treated mice. Ccl4 stimulation has led to brain barrier disruption in vivo and in vitro ( 43 ), which can lead to increased PVM macrophage infiltration. Interestingly, in the PMX205 treated mice, both microglia 13 and 16 are sources of App signaling, which ligates to Cd74 receptors in PVM macrophages ( Fig.…”
Section: Resultsmentioning
confidence: 99%